Strategy of Strengthening Institutional Fishermen Groups for Increasing Income - Agunggunanto, Edy Yusuf; Darwanto, Darwanto (JEJAK: Jurnal Ekonomi dan Kebijakan, 2016)
The community development and empowerment are two inseparable sides in the efforts to overcome the phenomenon of the fishermen communities, especially in the efforts to increase the welfare through the increasing income in the fishermen communities. One of the media in implementing the community development and empowerment is through the fishermen groups. The role of fishermen groups has not run optimally yet in improving the fishermenâs welfare, so it requires a strategy of developing the fishermen groups through the strategy of strengthening the economy in order to increase the fishermenâs income. This research aims to determine the priority of aspects to determine the strategies and to analyze the priority of strategy of strengthening the economy through the development of the institutional fishermen groups in order to increase the fishermen income in Central Java. The method of analysis in this research uses the Analytic Hierarchy Process (AHP). The result of AHP analysis indicates the priority of aspects in the strategy of strengthening the economy those are: aspects of participation,aspects of capital, aspects of partnership, and aspects of technology. The priority of alternatives in the strategy of strengthening the fishermenâs economy shows three sequences of 12 alternatives of strategies those are:Â  theÂ  socialization of the importance of groups, the increase in the active participation, and the increase in the number of meetings.